Teaching Writing Recount Text Through Photo Diary To The Eighth Grade Students - Hartini Agustiawati (Universitas Indo Global Mandiri, 2019)
AbstractThe main problem was the effectiveness to teach writing recount text through photo diary and the differences in achievement between students who were taught through photo diary and those who were not. Therefore, the objective of this study to find out whether it was effective or not to teach writing recount text through photo diary and to know the differences in achievement between the students who were taught by using photo diary and those who were not. The experimental method was used in this study. The population of this study was the eighth grade students of Junior high school number 5 with 74 students as the sample total numbers, which were divided into two groups, 37 students from experimental group and 37 students from control group. The data were collected through essay tests, pretest and posttest. The results showed that it was effective to teach writing recount text through photo diary, there were some differences in achievement between students who were taught through photo diary and without photo diary. It also indicated that photo diary could improve the students writing skills recount text. It is also suggested for teachers and researchers who want to teach and do research about writing especially Recount Text.Keywords : Teaching, Writing, Recount Text, Photo DiaryAbstrakMasalah utama adalah keefektifan mengajar menulis teks recount melalui photo diary dan perbedaan prestasi antara siswa yang diajar melalui photo diary dan mereka yang tidak. Oleh karena itu, tujuan penelitian ini untuk mengetahui apakah efektif atau tidak untuk mengajar menulis teks recount melalui photo diary dan untuk mengetahui perbedaan prestasi belajar antara siswa yang diajar dengan menggunakan photo diary dan yang tidak. Metode eksperimental digunakan dalam penelitian ini. Populasi penelitian ini adalah siswa kelas VIII SMP nomor 5 dengan jumlah siswa 74 sampel, yang dibagi menjadi dua kelompok, 37 siswa dari kelompok eksperimen dan 37 siswa dari kelompok kontrol. Data dikumpulkan melalui tes esai, pretest dan posttest. Hasil penelitian menunjukkan bahwa itu efektif untuk mengajar menulis teks recount melalui photo diary, ada beberapa perbedaan dalam prestasi antara siswa yang diajar melalui photo diary dan tanpa photo diary. Ini juga menunjukkan bahwa diary foto dapat meningkatkan keterampilan menulis teks recount siswa. Juga disarankan bagi para guru dan peneliti yang ingin mengajar dan melakukan penelitian tentang penulisan terutama Teks Recount.Kata kunci : Pengajaran, Menulis, Teks Recount, Photo Diary